Partisipasi Masyarakat Dalam Pembentukan Peraturan Daerah - Praptanugraha Praptanugraha (Fakultas Hukum Universitas Islam Indonesia, 2008)
Public’s participation in the process of legislation of local government ordinances is an important aspect for the sake of accommodating and representing public’s interest. Moreover, the said participation is also considered as a reflection of the justice and fairness.